Cryptic insertion of MYC exons 2 and 3 into the immunoglobulin heavy chain locus detected by whole genome sequencing in a case of “MYC-negative” Burkitt lymphoma - Wagener, Rabea; Toprak, Umut; Seufert, Julian; Schlesner, Matthias (Haematologica, 2020)
The genetic hallmark of Burkitt lymphoma (BL) is a translocation juxtaposing the MYC-oncogene to one of the three immunoglobulin (IG) loci.[1][1] There is ongoing controversy whether IG- MYC negative “true” BL exist. Various studies have identified 2-22% of BL as “ MYC -negative”.[2][2]-[5
Gesehen am 29.04.2020